Rising rates of bilateral mastectomy with reconstruction following neoadjuvant chemotherapy. Issue 12 (27th September 2018) - Pollom, Erqi L.; Qian, Yushen; Chin, Alexander L.; Dirbas, Frederick M.; Asch, Steven M.; Kurian, Allison W.; Horst, Kathleen C.; Tsai, C.Jillian
Abstract : Neoadjuvant chemotherapy (NAC) is used to allow more limited breast surgery without compromising local control. We sought to evaluate nationwide surgical trends in patients with operable breast cancer treated with NAC and factors associated with surgical type. We used the National Cancer Database to identify 235, 339 women with unilateral T1‐3 N0‐3 M0 breast cancer diagnosed between 2010 and 2014 and treated with surgery and chemotherapy. Of these, 59, 568 patients (25.3%) were treated with NAC. Rates of pathological complete response (pCR) to NAC increased from 33.3% at the start of the study period in 2010 to 46.3% at the end of the period in 2014 ( p = 0.02). Rates of breast‐conserving surgery (BSC) changed little, from 37.0 to 40.8% ( p = 0.22). Although rates of unilateral mastectomy decreased from 43.3 to 34.7% ( p = 0.02) and rates of bilateral mastectomy without immediate reconstruction remained similar (11.7–11.5%; p = 0.82), rates of bilateral mastectomy with immediate reconstruction rose from 8.0 to 13.1% ( p = 0.02). Patients who were younger, with private/managed care insurance, and diagnosed in more recent years were more likely to achieve pCR; however, these same characteristics were associated with receipt of bilateral mastectomy ( vs . BCS). In addition, non‐Hispanic white ethnic and higher area education attainment were both associated with bilateral mastectomy. These findings did not differ by age or molecular subtype. Further study of nonclinical factors that influence selection of more extensive surgery despite excellent response to NAC is warranted. Abstract : What's new? Bilateral mastectomy has been increasing among breast cancer patients who are otherwise candidates for breast‐conserving surgery (BCS), raising questions as to what drives decision‐making in this population. In this nationwide cohort study, bilateral mastectomy was more common among younger patients from a more advantaged sociodemographic background, even though these characteristics were associated with pathologic complete response. Being non‐Hispanic white, living in more highly‐educated areas, and having private insurance were independently associated with bilateral mastectomy. Improved understanding of characteristics associated with selecting mastectomy over BCS when BCS is appropriate would help clarify whether these decisions are toward personalized medicine or overtreatment.